Pemberdayaan Mahasiswa TRMG Unisbank dalam Produksi Video Promosi Potensi Lokal Menggunakan Aplikasi Kdenlive - Yunus Yunus Anis; Sri Mulyani; Hersatoto Listiyono; Sunardi (JURNAL ABDIMAS SERAWAI, 2026)
Local potentials such as tourist villages, MSME products, and cultural wisdom have high economic and social value, but are not yet fully supported by attractive and effective digital promotional media. On the other hand, students of the Graphic Multimedia Engineering Technology (TRMG) Study Program at Stikubank University (Unisbank) have great potential as creative agents in supporting the promotion of local potential, especially through the production of audiovisual content. This Community Service Activity aims to empower Unisbank TRMG students in producing promotional videos for local potential using the Kdenlive application as an open-source video processing software. The implementation method of the activity includes needs analysis, material preparation, technical training in video editing, promotional video production practice, as well as mentoring and evaluation of student work. The results of the activity show an increase in student competency in aspects of content planning, shooting techniques, and video processing using Kdenlive. In addition, students succeeded in producing several promotional videos for local potential that are worthy of being published through digital media. This activity not only has a positive impact on improving student skills but also contributes to efforts to promote the local potential of partners more effectively. Thus, the use of Kdenlive in community service activities has proven to be a means of empowering students while supporting the strengthening of the role of universities in developing a digital technology-based society.